Catalyst for producing olefins by catalytic cracking of waste plastics, preparation method and application thereof

By using dual-function catalysts with components such as ZSM-5 molecular sieve and metal oxides, waste plastics catalytically crack the production of low-carbon olefins, improving the selectivity and yield of propylene, and solving the low selectivity and hydrogenation of propylene in the prior art The problem of high refining cost has achieved an efficient and economical catalytic cracking process.

CN116493039BActive Publication Date: 2025-02-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310230892.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-11
Publication Date
2025-02-11
Estimated Expiration
2043-03-11

AI Technical Summary

Technical Problem

In the prior art, when waste plastic catalytic cracking of production of low-carbon olefins, propylene has low selectivity, and conventional methods require hydrofining to remove chlorides, which increases investment and operational costs.

Method used

Using a dual-function catalyst including ZSM-5 molecular sieve, calcium oxide or magnesium oxide, rare earth metal oxide and other components, the production of chemicals such as ethylene, propylene, butene and other chemicals through one-step method, and has anti-inactivation and the properties of effective chloride removal.

Benefits of technology

The yield of propylene is increased to more than 37%, and the formation of chloroalkanes is effectively prevented, and the consumption cost of catalyst is reduced. It is suitable for the fluidized bed process of continuous reaction-regeneration cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004120419840000071
    Figure BDA0004120419840000071
  • Figure BDA0004120419840000081
    Figure BDA0004120419840000081
Patent Text Reader

Abstract

The present invention discloses a catalyst for producing olefins by catalytic cracking of waste plastics, and its preparation method and application, and belongs to the field of waste plastics treatment technology. In terms of mass fraction, the catalyst includes: 41-65% ZSM-5 molecular sieve, 3-9% second active component, 1-9% co-active component, and the balance is a carrier and an adhesive. The catalyst provided by the present invention can effectively catalytically crack waste plastics to produce chemicals such as ethylene, propylene, and butene (especially with a high propylene yield) in a one-step method, and the catalyst has the characteristics of strong anti-deactivation ability and effective removal of chlorides. At the same time, the catalyst raw material is cheap and easy to obtain, the production process is simple, the cost is low, and it has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste plastic treatment, and specifically relates to a catalyst for producing olefins by catalytic cracking of waste plastics, and a preparation method and application thereof. Background Art

[0002] With the rapid development of the plastics industry and the increasing demand for plastic products, the proportion of used plastic solid waste in urban solid waste is also increasing day by day. Conventional methods for the treatment of waste plastics include landfill, incineration, physical recycling and chemical conversion. Landfill is the most commonly used method for treating solid waste, but it wastes land resources, and as time goes by, harmful substances such as additives and plasticizers in the waste plastics after landfill will dissolve, causing secondary pollution to the environment; incineration is currently a more commonly used treatment method. The combustion calorific value of waste plastics is equivalent to that of fuel oil, and it can be converted into heat energy after incineration, but harmful gases such as CO2 and dioxins will be produced during the incineration process, which will increase carbon emissions and pollute the atmosphere; physical recycling is to clean the waste plastics, granulate them, melt them and reuse them, which has certain economic benefits, but due to the variety of recycled waste plastics, the composite recycled plastics obtained after melting and regeneration are unstable, and can only produce some low-end plastic products, and the quality and value are far lower than new plastics.

[0003] The chemical conversion method is to convert waste plastics into fuel oil or chemical raw materials through thermal cracking or catalytic cracking. It can not only alleviate the problem of resource shortage, but also will not cause secondary pollution to the environment. It is the best choice for reducing the amount of waste plastics and recycling them. At present, waste plastics, whether thermal cracking or catalytic cracking, are still mainly used to generate oil products. However, with the increasing number of new energy vehicles in China, the demand for oil products is on a downward trend, and chemicals such as low-carbon olefins still need to be imported. Therefore, the production of chemicals from waste plastics is an effective way to utilize waste plastics. In addition, since waste plastics contain polyvinyl chloride, the products generated by thermal cracking or catalytic cracking contain chlorides that affect product quality. The conventional method is to remove chlorides through hydrofining, but hydrofining and removal of chlorides require the construction of special equipment, which increases investment and operating costs, and seriously affects economic benefits.

[0004] Ethylene and propylene in low-carbon olefins are both important chemical raw materials. Among them, propylene is one of the basic raw materials for the three major synthetic materials, and its largest amount is used to produce polypropylene. In addition, propylene can be used to prepare acrylonitrile, propylene oxide, isopropanol, phenol, acetone, butanol, octanol, acrylic acid and its esters, propylene glycol, epichlorohydrin and synthetic glycerol. If waste plastics can be converted into products such as propylene, huge economic benefits will be generated. In the prior art, patent document CN113398982B discloses a catalyst for preparing low-carbon olefins from waste plastics, which has a high liquefied gas yield, but the main products are propylene and butene, and the selectivity of propylene is relatively low; patent document CN112316986A provides a catalyst for producing low-carbon olefins and aromatics from waste plastics, and the low-carbon olefins are mainly ethylene. In general, in the prior art, the selectivity of propylene in the product distribution of low-carbon olefins from waste plastics still needs to be further improved. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a catalyst for catalytic cracking of waste plastics to produce olefins, as well as a preparation method and application thereof. The catalyst can effectively catalytically crack waste plastics to produce chemicals such as ethylene, propylene, butene (especially high propylene yield) in one step, and the catalyst has the characteristics of strong resistance to deactivation and effective removal of chlorides.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a catalyst for catalytic cracking of waste plastics to produce olefins, the catalyst comprising: a first active component, a second active component, a co-active component, a carrier and a binder;

[0008] Wherein, the first active component is ZSM-5 molecular sieve;

[0009] Wherein, the second active component is selected from one or both of calcium oxide and magnesium oxide.

[0010] As a further preferred embodiment of the technical solution of the present invention, the contents of the components are as follows, by mass fraction: 41-65% ZSM-5 molecular sieve, 3-9% second active component, 1-9% co-active component, and the remainder is carrier and binder.

[0011] As a further preferred embodiment of the technical solution of the present invention, the silicon-aluminum ratio of the ZSM-5 molecular sieve is 75-300; preferably, the silicon-aluminum ratio is 90-150.

[0012] As a further preferred embodiment of the technical solution of the present invention, the auxiliary active component is selected from a combination of one or more of rare earth metal oxides, phosphorus oxide, and boron oxide.

[0013] As a further preferred embodiment of the technical solution of the present invention, the rare earth oxide is cerium oxide.

[0014] As a further preferred embodiment of the technical solution of the present invention, the cerium oxide is obtained by decomposing cerium chloride or cerium nitrate; the calcium oxide is obtained by decomposing calcium chloride or calcium nitrate; and the magnesium oxide is obtained by decomposing magnesium chloride or magnesium nitrate.

[0015] As a further preferred embodiment of the technical solution of the present invention, the binder is selected from one or both of aluminum sol and silica sol; the carrier is selected from one or more of silicon oxide, kaolin, attapulgite, bentonite and diatomaceous earth.

[0016] In a second aspect, the present invention provides a method for preparing the above catalyst, characterized in that it comprises the following steps:

[0017] After deionized water and a binder are stirred evenly, a carrier is added and stirred evenly again; then, a ZSM-5 molecular sieve is added and stirred evenly again to obtain a sol, and then an auxiliary active component is added to the sol and stirred to obtain a solution 1;

[0018] Add the second active component to deionized water and stir evenly to obtain solution 2;

[0019] Solution 2 is added to solution 1, and after stirring, the mixture is filtered and ground to obtain solution 3;

[0020] The solution 3 is molded, dried and calcined to obtain a finished catalyst.

[0021] As a further preferred embodiment of the technical solution of the present invention, the specific steps of molding, drying and calcining are: sending the obtained solution 3 into a spray drying tower for treatment to obtain a molded catalyst, with a furnace temperature of 350-550°C, an outlet temperature of 150-350°C, and a spray pressure of 2-5MPa; then, drying the molded catalyst at 150-250°C for 2-6h, and after drying, calcining at 450-600°C for 2-6h to obtain a finished catalyst.

[0022] In a third aspect, the present invention provides a use of the above catalyst in preparing olefins from waste plastics.

[0023] As a further preferred embodiment of the technical solution of the present invention, the above-mentioned olefin product is propylene.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The bifunctional catalyst of the present invention can directly catalytically crack waste plastics to produce chemicals such as ethylene, propylene, and butene.

[0026] (2) The bifunctional catalyst molecular sieve of the present invention has a high content of active components, and has a high yield of producing ethylene, propylene, butene, etc. by directly catalytic cracking of waste plastics, and the maximum yield of propylene can reach 37%+.

[0027] (3) The bifunctional catalyst of the present invention can convert the hydrogen chloride generated during the catalytic cracking of waste plastics into metal chlorides in situ, effectively preventing the generation of chloroalkanes.

[0028] (4) The bifunctional catalyst of the present invention has good hydrothermal stability and a long service life due to modification of the biactive components.

[0029] (5) The preparation process of the bifunctional catalyst of the present invention utilizes aluminum sol as a binder and is compounded with a catalyst carrier such as kaolin. When the catalyst molecular sieve content is high, the catalyst still has good anti-wear performance, effectively reducing the consumption cost of the catalyst.

[0030] (6) The bifunctional catalyst of the present invention is suitable for a fluidized bed process with a continuous reaction-regeneration cycle, and the activity of the catalyst is maintained by continuous addition and discharge of the catalyst.

[0031] (7) The raw materials of the bifunctional catalyst of the present invention are cheap and easily available, the production process is simple and the cost is low. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Meanwhile, it should be emphasized that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturers are not specified, are all conventional products that can be purchased commercially.

[0034] In the present invention, a catalyst for producing olefins by catalytic cracking of waste plastics comprises: a first active component, a second active component, an auxiliary active component, a carrier and a binder;

[0035] Wherein, the first active component is ZSM-5 molecular sieve;

[0036] Wherein, the second active component is selected from one or both of calcium oxide and magnesium oxide.

[0037] In the above technical scheme, the catalyst is a bifunctional catalyst, one of the active components is ZSM-5 molecular sieve, and the cracking reaction of waste plastics such as polyethylene (PE) and polypropylene (PP) on ZSM-5 molecular sieve solid acid catalyst follows the classic carbon ion reaction mechanism. First, the long-chain olefins produced by thermal cracking of the polymer obtain protons H from the B acid site on the catalyst surface. + The carbon ions are generated, which then undergo β-cleavage to generate smaller molecular olefins, or the carbon ions act as intermediates in other secondary reactions to undergo isomerization, cyclization, aromatization and other reactions to generate alkanes, olefins, aromatics and other compounds.

[0038] PVC waste plastics also undergo similar reactions on ZSM-5 molecular sieve solid acid catalysts, but hydrogen chloride is also generated at the same time. Hydrogen chloride reacts with olefin molecules generated by catalytic cracking of waste plastics to produce addition reactions, resulting in both gaseous and liquid products containing chloroalkanes, which seriously affects product quality.

[0039] Another active component of the bifunctional catalyst is a metal oxide (selected from one or both of calcium oxide and magnesium oxide), which can react in situ with hydrogen chloride generated by catalytic cracking of waste plastics to generate metal chloride, thereby blocking the reaction of hydrogen chloride with olefins to generate chloroalkane polluting products.

[0040] In the catalyst of the present invention, the ZSM-5 molecular sieve has the function of catalytically cracking waste plastics to generate low-carbon olefins; the function of the second active component metal oxide is to convert hydrogen chloride generated in the process of catalytic cracking of waste plastics into metal salts in situ to remove hydrogen chloride; the auxiliary active components rare earth metal oxide, phosphorus oxide, boron oxide and the like can improve the hydrothermal stability of the active component ZSM-5 molecular sieve in the process of high-temperature regeneration, because the molecular sieve modified with oxides such as rare earth metal oxide, phosphorus oxide, boron oxide and the like has a crystal volume shrinkage tendency greatly slowed down in a high-temperature water vapor environment, and the modification can weaken the strong acid center of the molecular sieve and is also conducive to improving the selectivity of low-carbon olefins; at the same time, the rare earth metal oxide, phosphorus oxide and boron oxide can form a weak binding force with the second active component metal oxide, can effectively alleviate the aggregation of the high-content second active component metal oxide in the process of high-temperature regeneration, retain its dispersion to the maximum extent, and play a role in effectively capturing hydrogen chloride; the function of the carrier is to provide a good dispersion matrix for the catalyst and provide suitable wear strength and particle shape, etc., to meet the needs of normal fluidization of the catalyst in the fluidized bed reactor.

[0041] In some embodiments, in the above catalyst, the content of each component is as follows, by mass fraction: 41-65% ZSM-5 molecular sieve, 3-9% second active component, 1-9% co-active component, and the remainder is carrier and binder. Preferably, the content of ZSM-5 molecular sieve is 45-55%. It can be understood that its content can be any specific value among 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, or any value within the range of 45-55%. Preferably, the amount of the second active component is 5-7.5%. It can be understood that its content can be any specific value among 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, or any value within the range of 5-7.5%.

[0042] In some embodiments, the silicon-aluminum ratio of the ZSM-5 molecular sieve is 75 to 300; preferably, the silicon-aluminum ratio is 90 to 150. It is understood that the silicon-aluminum ratio can be any specific value of 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150 or any value within the range of 90 to 150.

[0043] In some embodiments, the auxiliary active component is selected from a combination of one or more of rare earth metal oxides, phosphorus oxide, and boron oxide. Preferably, the rare earth metal oxide is cerium oxide; preferably, the auxiliary active component is a combination of cerium oxide and phosphorus oxide; further preferably, the content of cerium oxide is 1-5%; the content of phosphorus oxide is 0.5-3.5%; more preferably, the content of cerium oxide is 2-3.5%, and the content of phosphorus oxide is 1-2%. It can be understood that the content of cerium oxide can be any specific value among 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, or any value within the range of 2 to 3.5%; the content of phosphorus oxide can be any specific value among 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, or any value within the range of 1 to 2%.

[0044] In some embodiments, the source of the cerium oxide can be directly cerium oxide, or it can be obtained by decomposing cerium chloride or cerium nitrate; calcium oxide can be directly calcium oxide, or it can be obtained by decomposing calcium chloride or calcium nitrate; magnesium oxide can be directly magnesium oxide, or it can be obtained by decomposing magnesium chloride or magnesium nitrate.

[0045] In some embodiments, the binder is selected from one or both of aluminum sol or silica sol, preferably aluminum sol; the carrier is selected from one or more of silicon oxide, kaolin, attapulgite, bentonite, diatomaceous earth, preferably kaolin. The content of the binder is 15-30%, preferably 20-25%; the content of the carrier is 10-30%, preferably 15-20%. It is understood that the content of the binder can be any specific value of 20%, 21%, 22%, 23%, 24%, 25% or any value in the range of 20-25%; the content of the carrier can be any specific value of 15%, 16%, 17%, 18%, 19%, 20% or any value in the range of 15-20%.

[0046] In some embodiments, a method for preparing the above catalyst is also provided, comprising the following steps:

[0047] After deionized water and a binder are stirred evenly, a carrier is added and stirred evenly again; then, a ZSM-5 molecular sieve is added and stirred evenly again to obtain a sol, and then an auxiliary active component is added to the sol and stirred to obtain a solution 1;

[0048] Add the second active component to deionized water and stir evenly to obtain solution 2;

[0049] Solution 2 is added to solution 1, and after stirring, the mixture is filtered and ground to obtain solution 3;

[0050] The solution 3 is molded, dried and calcined to obtain a finished catalyst.

[0051] In some embodiments, the specific steps of molding, drying and calcining are: sending the obtained solution 3 into a spray drying tower for treatment to obtain a molded catalyst, with a furnace temperature of 350-550°C, an outlet temperature of 150-350°C, and a spray pressure of 2-5MPa; then, drying the molded catalyst at 150-250°C for 2-6 hours, and after drying, calcining at 450-600°C for 2-6 hours to obtain a finished catalyst. It can be understood that the furnace temperature can be any specific value of 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or any value in the range of 350-550°C; the outlet temperature can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, Any specific value among 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃, 290℃, 300℃, 310℃, 320℃, 330℃, 340℃, 350℃ or any value within the range of 150-350℃; the spray pressure can be 2MPa, 2.2MPa, 2.4MPa, 2.6MPa, 2.8MPa, 3MPa, 3.2MPa, 3.4MPa, 3.6MPa, 3.8MPa, 4MPa, 4.2MPa, 4.4MPa , 4.6MPa, 4.8MPa, 5MPa, or any value in the range of 2-5MPa; the catalyst drying temperature can be any specific value among 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, or any value in the range of 150-250°C; the drying time can be any specific value among 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, or any value in the range of 2- The calcination temperature may be any specific value among 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, or any value within the range of 450~600℃; the calcination time may be any specific value among 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, or any value within the range of 2~6h.

[0052] In some embodiments, the present invention also provides a use of the above catalyst in catalytic preparation of olefins, especially propylene, from waste plastics.

[0053] It should be particularly emphasized that the waste plastics mentioned in the present invention may be hydrocarbon plastics, generally one or more of polyethylene, polypropylene, polyvinyl chloride, ethylene-propylene copolymer, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-cycloolefin copolymer, polydicyclopentadiene, cyclopentadiene copolymer, and polystyrene.

[0054] The catalyst for producing olefins by catalytic cracking of waste plastics and its preparation method and application are further described below in conjunction with specific embodiments.

[0055] Example 1

[0056] A method for preparing a catalyst for producing olefins by catalytic cracking of waste plastics, comprising:

[0057] 8000 kg of deionized water and 11900 kg of aluminum sol were stirred for 1 hour, and then 2700 kg of kaolin was added, and the mixture was stirred for another 4 hours; then 5000 kg of ZSM-5 molecular sieve with a silicon-aluminum ratio of 120 was added, and the mixture was stirred for another 6 hours to obtain a sol, and then 240 kg of 85% phosphoric acid and 750 kg of cerium nitrate hexahydrate were added to the sol, and the mixture was stirred for another 4 hours to obtain a solution 1;

[0058] Add 1500 kg of magnesium nitrate to 5000 kg of deionized water and stir for 2 hours to obtain solution 2;

[0059] Solution 2 was added to solution 1, and the mixture was stirred for 2 h, filtered, and ground to obtain solution 3;

[0060] The above solution 1 is sent to a spray drying tower for treatment to obtain a shaped catalyst, with a furnace temperature of 450°C, an outlet temperature of 180°C, and a spray pressure of 4MPa; then, the shaped catalyst is dried at 150°C for 4h, and after drying, it is calcined at 550°C for 6h to obtain a finished catalyst.

[0061] Example 2

[0062] A method for preparing a catalyst for producing olefins by catalytic cracking of waste plastics, comprising:

[0063] 5000 kg of deionized water and 11900 kg of aluminum sol were stirred for 1 hour, and then 2000 kg of kaolin was added, and the mixture was stirred for another 4 hours; then 5000 kg of ZSM-5 molecular sieve with a silicon-aluminum ratio of 120 was added, and the mixture was stirred for another 6 hours to obtain a sol, and then 240 kg of 85% phosphoric acid and 750 kg of cerium nitrate hexahydrate were added to the sol, and the mixture was stirred for another 4 hours to obtain a solution 1;

[0064] Add 1500 kg of calcium nitrate to 5000 kg of deionized water and stir for 2 hours to obtain solution 2;

[0065] Solution 2 was added to solution 1, and the mixture was stirred for 2 h, filtered, and ground to obtain solution 3;

[0066] The above solution 3 is sent to a spray drying tower for treatment to obtain a shaped catalyst, with a furnace temperature of 450°C, an outlet temperature of 180°C, and a spray pressure of 4MPa; then, the shaped catalyst is dried at 150°C for 4h, and after drying, it is calcined at 550°C for 6h to obtain a finished catalyst.

[0067] Example 3

[0068] A method for preparing a catalyst for producing olefins by catalytic cracking of waste plastics, comprising:

[0069] 5000 kg of deionized water and 11900 kg of aluminum sol were stirred for 1 hour, and then 1800 kg of kaolin was added, and the mixture was stirred for another 4 hours; then 5000 kg of ZSM-5 molecular sieve with a silicon-aluminum ratio of 120 was added, and the mixture was stirred for another 6 hours to obtain a sol; then 240 kg of 85% phosphoric acid and 750 kg of cerium nitrate hexahydrate were added to the sol, and the mixture was stirred for another 4 hours to obtain a solution 1;

[0070] Add 2000 kg of calcium nitrate to 5000 kg of deionized water and stir for 2 hours to obtain solution 2;

[0071] Solution 2 was added to solution 1, and the mixture was stirred for 2 h, filtered, and ground to obtain solution 3;

[0072] The above solution 3 is sent to a spray drying tower for treatment to obtain a shaped catalyst, with a furnace temperature of 450°C, an outlet temperature of 180°C, and a spray pressure of 4MPa; then, the shaped catalyst is dried at 150°C for 4h, and after drying, it is calcined at 550°C for 6h to obtain a finished catalyst.

[0073] Comparative Example 1

[0074] A method for preparing a catalyst for producing olefins by catalytic cracking of waste plastics, comprising:

[0075] 5000 kg of deionized water and 11900 kg of aluminum sol were stirred for 1 hour, and then 2000 kg of kaolin was added, and the mixture was stirred for another 4 hours; then 5000 kg of ZSM-5 molecular sieve with a silicon-aluminum ratio of 120 was added, and the mixture was stirred for another 6 hours to obtain a sol, and then 240 kg of 85% phosphoric acid and 750 kg of cerium nitrate hexahydrate were added to the sol, and the mixture was stirred for another 4 hours to obtain a solution 1;

[0076] The above solution 1 is sent to a spray drying tower for treatment to obtain a shaped catalyst, with a furnace temperature of 450°C, an outlet temperature of 180°C, and a spray pressure of 4MPa; then, the shaped catalyst is dried at 150°C for 4h, and after drying, it is calcined at 550°C for 6h to obtain a finished catalyst.

[0077] That is, compared with Example 2, the addition of the second active component was omitted in this comparative example, and the preparation method steps were omitted accordingly.

[0078] The product properties of the catalysts prepared in Examples 2 to 3 and Comparative Example 1 are as follows:

[0079] Table 1 Physical properties of catalysts

[0080]

[0081] As can be seen from Table 1, the catalyst prepared by the present invention has a suitable bulk density and particle size distribution as well as a high specific surface area and pore volume, and can be well adapted to the fluidization requirements of the reaction process of the fluidized bed reactor; when the catalyst molecular sieve content is about 50%, it still has good wear resistance (industrial applications generally require a wear index of ≤3%), which can ensure that the catalyst has a low loss during the fluidization process.

[0082] Application Examples

[0083] The catalysts prepared in Examples 2 to 3 and Comparative Example 1 were used to produce olefins from waste plastics. The specific test method is as follows: The test was conducted on a 10ml fixed bed reactor test device, the raw material was polypropylene particles plus about 1% polyvinyl chloride particles, and the overall chlorine content was 0.5%. The test conditions were normal pressure, 500°C, and a feed space velocity of 1.0h -1 The ratio of atomized water vapor to plastic particles is 0.5:1. The test results are shown in Table 2 below.

[0084] Table 2 Catalytic cracking test results of prepared catalysts, wt%

[0085]

[0086] Note: CnHmCl refers to the chloroalkane generated during the reaction

[0087] As can be seen from Table 2, the catalytic cracking of polypropylene (containing a small amount of polyvinyl chloride) using the prepared bifunctional catalyst can produce low-carbon olefins such as ethylene, propylene, and butene, with a total olefin yield of more than 65%; the oil product yield is about 20%, of which the main component is aromatics; in addition, the prepared bifunctional catalyst has a good dechlorination function, with a dechlorination rate of more than 97%, and both the gaseous products and liquid products after dechlorination can be directly used.

[0088] In summary, the bifunctional catalyst of the present invention with ZSM-5 molecular sieve and alkaline earth metal oxide as active components is a good catalyst for direct production of chemicals such as ethylene, propylene, butene and direct dechlorination by catalytic cracking of waste plastics, especially with the highest yield of propylene. Under appropriate process conditions, catalytic cracking of waste plastics can produce more than 65% of low-carbon olefins (the highest propylene yield reaches 37.6%), and the catalyst dechlorination rate exceeds 97%. The bifunctional catalyst has good hydrothermal stability and anti-wear performance through modification of the dual active components, which can effectively reduce the consumption cost of the catalyst; the physical properties of the bifunctional catalyst can meet the needs of the fluidized bed process of continuous reaction-regeneration cycle.

[0089] The present invention illustrates the technical concept of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. Use of a catalyst in preparing olefins from waste plastics, characterized in that: The waste plastic contains polyvinyl chloride, and the catalyst comprises: a first active component, a second active component, an auxiliary active component, a carrier and an adhesive; Wherein, the first active component is ZSM-5 molecular sieve; Wherein, the second active component is selected from one or both of calcium oxide and magnesium oxide; The contents of the components are as follows, by mass fraction: 41-65% ZSM-5 molecular sieve, 3-9% second active component, 1-9% auxiliary active component, and the remainder is carrier and binder; Wherein, the auxiliary active component is selected from a combination of one or more of rare earth metal oxides, phosphorus oxide, and boron oxide; Wherein, the rare earth oxide is cerium oxide; The binder is selected from one or both of aluminum sol and silica sol; the carrier is selected from one or more of silicon oxide, kaolin, attapulgite, bentonite and diatomaceous earth.

2. The use according to claim 1, characterized in that: The silicon-aluminum ratio of ZSM-5 molecular sieve is 90-150.

3. The use according to claim 1, characterized in that: The cerium oxide is obtained by decomposing cerium chloride or cerium nitrate; the calcium oxide is obtained by decomposing calcium chloride or calcium nitrate; and the magnesium oxide is obtained by decomposing magnesium chloride or magnesium nitrate.

4. The use according to any one of claims 1 to 3, characterized in that: The preparation of the catalyst comprises the following steps: After deionized water and a binder are stirred evenly, a carrier is added and stirred evenly again; then, a ZSM-5 molecular sieve is added and stirred evenly again to obtain a sol, and then an auxiliary active component is added to the sol and stirred to obtain a solution 1; Add the second active component to deionized water and stir evenly to obtain solution 2; Solution 2 is added to solution 1, and after stirring, the mixture is filtered and ground to obtain solution 3; The solution 3 is molded, dried and calcined to obtain a finished catalyst.

5. The use according to claim 4, characterized in that: The specific steps of molding, drying and roasting are: The obtained solution 3 is sent to a spray drying tower for treatment to obtain a shaped catalyst, with a furnace temperature of 350-550°C, an outlet temperature of 150-350°C, and a spray pressure of 2-5MPa; then, the shaped catalyst is dried at 150-250°C for 2-6h, and after drying, it is calcined at 450-600°C for 2-6h to obtain a finished catalyst.

6. The use according to claim 5, characterized in that: The olefin is propylene.

Citation Information

Patent Citations

  • Catalyst and preparation method and application thereof

    CN112316986A

  • A catalyst for the catalytic cracking of waste plastics to produce low-carbon olefins and its preparation method.

    CN113398982B

  • Catalytic cracking assistant for propylene yield increase

    CN102872902A

  • Processing method and system of waste plastics

    CN114106865A

  • Method for producing propylene, ethene by using catalytic cracking olefin through fluid bed

    CN1915925A